Quantitative Estimation of Adsorbed Water Layer on Austenitic Stainless Steel - Zaid Ali Subhi; Kanao Fukuda; Takehiro Morita; Joichi Sugimura (Tribology Online, 2015)
A study was carried out to estimate the thickness of the adsorbed water layer on the surface of austenitic stainless steel (JIS SUS316) in different atmospheric humidity conditions. The purpose of the study is to have a quantitative data on water adsorption that has influences on the tribological phenomena. The mass of stainless steel plate was determined by the weighting method as a function of the relative humidity (RH) in ambient atmospheric air. An experimental device consisting of atmospheric humidity controller and high sensitivity analytical balance with affixed airtight chamber was used for the purpose of the study. The result of water adsorption progression on SUS316 surface has been discussed and schematically demonstrated. It is clarified that the thickness of adsorbed water is significantly large to influence the tribological properties as demonstrated in a schematic model of the interface state of pin-on-disk prior to contact in high RH.